Lithium secondary battery
By using silicon-based negative electrodes and electrolytes with specific additives in lithium secondary batteries, the problem of large gas generation at high temperatures is solved, and high capacity, low resistance and excellent cycling performance are achieved.
Patent Information
- Application Number
- CN202380054909.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-22
- Filing Date
- 2023-12-25
- Publication Date
- 2025-02-25
AI Technical Summary
While using silicon-based negative electrodes to achieve high capacity, it is difficult for the prior art to maintain battery resistance, improve high temperature cycling performance, and reduce the amount of gas generated during storage.
By using an electrolyte containing a silicon-based negative electrode and a specific additive in a lithium secondary battery, the composition and content of the electrolyte are adjusted to reduce the amount of gas generated at high temperatures while maintaining battery performance.
It is achieved to reduce the amount of gas generation during long-term storage at high temperatures, maintain the high capacity and energy density of the battery, and improve the cycling performance of the battery.
Smart Images

Figure CN119522497A_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0187433 filed in the Korean Intellectual Property Office on December 28, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a lithium secondary battery. Background Art
[0003] As a part of the increasing demand for the use of alternative or clean energy due to the rapid increase in the use of fossil fuels, the most active research field is the field of power generation and storage using electrochemical reactions.
[0004] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and their use range tends to be gradually expanded.
[0005] With the development of technology and the growth of demand for mobile devices, the demand for secondary batteries as energy sources has grown rapidly. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as such high-capacity lithium secondary battery electrodes, methods for manufacturing high-density electrodes with higher energy density per unit volume are being actively studied.
[0006] Typically, a secondary battery comprises a positive electrode, a negative electrode, an electrolyte and a separator. The negative electrode comprises a negative electrode active material that embeds and deintercalates lithium ions from the positive electrode. As a negative electrode material, carbon-based materials such as graphite have excellent stability and reversibility, but there are limitations in terms of capacity. Therefore, in the field of high capacity, attempts to use Si-based materials with high theoretical capacity as negative electrode materials are increasing.
[0007] That is, lithium secondary batteries are usually manufactured by using compounds embedded with lithium, such as LiCoO2 or LiMn2O4, for the positive electrode and materials not embedded with lithium, such as carbon or Si materials, for the negative electrode. During charging, the lithium ions embedded in the positive electrode move to the negative electrode through the electrolyte. During discharge, the lithium ions move back to the positive electrode from the negative electrode. During charging, the lithium moving from the positive electrode to the negative electrode reacts with the electrolyte, thereby forming a passivation film, i.e., a solid electrolyte interface (SEI), on the surface of the negative electrode. SEI inhibits the transmission of electrons required for the reaction of the negative electrode with the electrolyte, thereby preventing the electrolyte from decomposing, thereby stabilizing the structure of the negative electrode. On the other hand, the formation of SEI is irreversible, resulting in the consumption of lithium ions. That is, the lithium consumed due to the formation of SEI will not return to the positive electrode during the subsequent discharge process, resulting in a decrease in the capacity of the battery.
[0008] On the other hand, as an effort to improve the performance of lithium secondary batteries, it is necessary to develop technologies that accelerate the charging rate. In order to quickly charge lithium secondary batteries, the migration rate of lithium ions should be fast during the process of lithium ion embedding into the negative electrode. Therefore, battery design is being carried out to shorten the diffusion distance of lithium by forming a negative electrode active material layer with a thickness of a film level, and to increase conductivity by forming a carbon coating layer on the surface of the negative electrode active material layer, thereby reducing internal resistance, thereby achieving high output.
[0009] However, it is difficult to achieve high capacity using a negative electrode having such a thin film negative electrode active material layer. In addition, it is difficult to achieve fast charging in a negative electrode with high capacity. In addition, when a silicon-based negative electrode is used, in order to increase the energy density, the Si content in the negative electrode is increased. Therefore, due to the reduced efficiency of the high Ni positive electrode as a positive electrode material, an excessive amount of sacrificial positive electrode material is applied to balance with the negative electrode. However, in this case, the gas generation of the battery cell itself is increased and the resulting stability problem is caused.
[0010] In general, carbonate compounds containing fluorine groups are limitedly used for solvents contained in electrolytes of lithium secondary batteries. That is, the carbonate compounds containing fluorine groups are contained in order to ensure the ionic conductivity of the electrolyte, but when the carbonate compounds are used in excess, problems such as increased production of Lewis acids and increased gas generation occur. Therefore, in the relevant field, although carbonate compounds containing fluorine groups have advantages, carbonate compounds containing fluorine groups are contained in a lower content, and materials with high dielectric constants such as PC are used to compensate for the resulting ionic conductivity. However, even in this case, the problem of gas generation at high temperatures has not been solved.
[0011] Therefore, research is required on maintaining battery resistance, improving high temperature cycle performance, and reducing the amount of gas generated during storage while using a negative electrode including a silicon-based active material to achieve high capacity.
[0012] Prior art documents
[0013] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention
[0014] Technical issues
[0015] As a result of research on the above problems, it was found that when using a silicon-based negative electrode to ensure capacity characteristics and fast charging performance while adjusting the specific composition and content of the electrolyte, the battery resistance can be maintained, the high-temperature cycle performance can be improved, and the gas generation amount during storage can be reduced. That is, it was found that the electrolyte is the main factor for gas generation during long-term storage at high temperatures, and adjusting the composition and content of the electrolyte can reduce the amount of generated gas without affecting the performance of the lithium secondary battery.
[0016] Therefore, the present application relates to a lithium secondary battery including a silicon-based negative electrode and an electrolyte containing a specific additive.
[0017] Technical Solution
[0018] An exemplary embodiment of the present specification provides a lithium secondary battery, including a positive electrode; a silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the silicon-based negative electrode includes a negative electrode current collector layer and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer includes a negative electrode active material layer composition, wherein the negative electrode active material layer composition includes a silicon-based active material, and the silicon-based active material includes at least one selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloy, wherein the electrolyte includes a solvent, a lithium salt, a fluorine-based additive, and vinylene carbonate (VC), wherein, based on 100 parts by weight of the electrolyte, the content of vinylene carbonate is 0.3 parts by weight or less, wherein, based on 100 parts by weight of the solvent, the content of a fluorine-containing carbonate compound is 10 parts by weight or more, and wherein, based on 100 parts by weight of the electrolyte, the content of the fluorine-based additive is 2 parts by weight or less.
[0019] Advantageous Effects
[0020] The lithium secondary battery according to the present application can ensure that the battery has a high capacity and a high energy density by using the silicon-based negative electrode, and can also form a negative electrode thickness at the thin film level by using a silicon-based active material with excellent capacity characteristics, thereby ensuring fast charging performance.
[0021] In particular, the lithium secondary battery according to the present application includes a solvent, a lithium salt, a fluorine-based additive, and vinylene carbonate (VC) as the electrolyte.
[0022] More specifically, the content of the carbonate compound containing a fluorine group is 10 parts by weight or more based on 100 parts by weight of the solvent, so that ion conductivity can be ensured. However, when the above solvent is used, the amount of gas generated increases, so the content of the fluorine-containing additive forming the "film derived from F" is set to the above parts by weight, and the content of vinylene carbonate having a low film-forming effect on the Si-based active material layer is reduced to the above range, thereby adjusting the amount of gas generated.
[0023] That is, vinylene carbonate does not form an effective film on the silicon-based negative electrode and remains, and a large amount of gas is generated due to the oxidation reaction at the positive electrode. Therefore, the content of vinylene carbonate is adjusted, and an additive that forms an effective film on the silicon-based negative electrode is included.
[0024] Therefore, the lithium secondary battery according to the present application has the characteristics of reducing the amount of gas generated to ensure performance even during long-term storage at high temperatures, and ensuring ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A lithium secondary battery according to the present application is shown.
[0026] <Description of symbols>
[0027] 10: Negative electrode collector layer
[0028] 20: Negative electrode active material layer
[0029] 30: Diaphragm
[0030] 40: Positive electrode active material layer
[0031] 50: Positive electrode collector layer
[0032] 100: Negative electrode
[0033] 200: Positive DETAILED DESCRIPTION
[0034] Before describing the present invention, some terms are first defined.
[0035] Unless otherwise specifically described, in the present specification, when a component “includes,” “contains,” or “has” a constituent element, this does not mean to exclude other constituent elements but means that other constituent elements may further be included.
[0036] In this specification, “p to q” means a range of “p or more and q or less”.
[0037] In this specification, "specific surface area" is measured by the BET method, specifically, calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) by using BELSORP-mini II available from BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.
[0038] In this specification, "Dn" means particle size distribution, and means the particle size at n% point in the cumulative distribution of the number of particles according to the particle size. That is, D50 is the particle size at 50% point in the cumulative distribution of the number of particles according to the particle size, D90 is the particle size at 90% point in the cumulative distribution of the number of particles according to the particle size, and D10 is the particle size at 10% point in the cumulative distribution of the number of particles according to the particle size. On the other hand, the particle size distribution can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac S3500), wherein when the laser beam passes through the particle, the difference in the diffraction pattern according to the particle size is measured, and then the particle size distribution is calculated.
[0039] In the present specification, the description "a polymer contains a specific monomer as a monomer unit" means that the monomer participates in a polymerization reaction and is contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, this is interpreted as the same as the polymer containing the monomer as a monomer unit.
[0040] In the present specification, it should be understood that the term "polymer" is used in a broad sense including copolymers unless otherwise specified as a "homopolymer".
[0041] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene conversion molecular weights measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specifically described, molecular weight refers to weight average molecular weight.
[0042] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.
[0043] An exemplary embodiment of the present specification provides a lithium secondary battery, comprising a positive electrode; a silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the silicon-based negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer comprises a negative electrode active material layer composition, wherein the negative electrode active material layer composition comprises a silicon-based active material, and the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloys, wherein the electrolyte comprises a solvent, a lithium salt, a fluorine-containing group additive, and vinylene carbonate (VC), wherein, based on 100 parts by weight of the electrolyte, the content of vinylene carbonate is 0.3 parts by weight or less, wherein, based on 100 parts by weight of the solvent, the content of a carbonate compound containing a fluorine group is 10 parts by weight or more, and wherein, based on 100 parts by weight of the electrolyte, the content of the fluorine-containing group additive is 2 parts by weight or less.
[0044] It has been found that the electrolyte is the main factor for gas generation during long-term storage at high temperatures, and adjusting the composition and content of the electrolyte can reduce the amount of gas generated without affecting the performance of the lithium secondary battery.
[0045] Therefore, the present application can ensure ionic conductivity by including 10 parts by weight or more of the carbonate compound containing a fluorine group based on 100 parts by weight of the solvent. However, when using the above solvent, the amount of gas generation increases. Therefore, the content of the fluorine-containing group additive that forms a "film derived from F" is set to the above parts by weight, and the content of vinylene carbonate with a low film-forming effect on the Si-based active material layer is reduced to the above range, thereby adjusting the amount of gas generation.
[0046] Figure 1 FIG. is a diagram showing the stacked structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, a negative electrode 100 including a negative electrode active material layer 20 on one surface of a negative electrode current collector layer 10 can be seen, a positive electrode 200 including a positive electrode active material layer 40 on one surface of a positive electrode current collector layer 50 can be seen, and the negative electrode 100 and the positive electrode 200 for the lithium secondary battery form a stacked structure with a separator 30 interposed therebetween.
[0047] The positive electrode, negative electrode, electrolyte, and separator included in the lithium secondary battery will be described separately below.
[0048] In an exemplary embodiment of the present application, the electrolyte may include a solvent, a lithium salt, a fluorine-containing group additive, and vinylene carbonate (VC).
[0049] A lithium secondary battery according to the present application relates to a composition of an electrolyte capable of reducing the amount of gas generation even during storage at high temperatures.
[0050] In an exemplary embodiment of the present application, as the solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate or ethyl propionate can be used.
[0051] In the present application, there is provided a lithium secondary battery in which the solvent is a mixed solvent containing two carbonate-based compounds.
[0052] Especially, in carbonate system mixed solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, and because their dielectric constant is high, thus dissociate lithium salt well, therefore can preferably use.When described cyclic carbonate and low viscosity and low dielectric constant linear carbonate such as dimethyl carbonate and diethyl carbonate are mixed with suitable ratio and used, can manufacture the high electrolyte of specific conductivity, therefore such combination use can be more preferred.
[0053] Particularly, in an exemplary embodiment of the present application, the content of the carbonate compound including a fluorine group is 10 parts by weight or more based on 100 parts by weight of the solvent.
[0054] In another exemplary embodiment, the content of the carbonate compound containing a fluorine group may be 10 parts by weight or more, preferably 12 parts by weight or more, more preferably 15 parts by weight or more, and may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, based on 100 parts by weight of the solvent.
[0055] In general, carbonate compounds containing fluorine groups are limitedly used for solvents contained in electrolytes of lithium secondary batteries. That is, the carbonate compounds containing fluorine groups are contained in order to ensure the ionic conductivity of the electrolyte, but when the carbonate compounds are used in excess, problems such as increased production of Lewis acids and increased gas generation occur. Therefore, in the relevant field, although carbonate compounds containing fluorine groups have advantages, the carbonate compounds containing fluorine groups are contained in a lower content, and materials with high dielectric constants such as PC are used to compensate for the resulting ionic conductivity. However, even in this case, the problem of gas generation at high temperatures has not been solved.
[0056] In the case of the electrolyte according to the present application, ion conductivity can be ensured by containing the fluorine-containing carbonate compound as a solvent in the above-mentioned amount by weight, and at the same time, the corresponding gas generation problem is solved by adjusting the content of vinylene carbonate described later and containing a specific content of the fluorine-containing additive.
[0057] In an exemplary embodiment of the present application, there is provided a lithium secondary battery in which the content of the fluorine-based additive is 2 parts by weight or less based on 100 parts by weight of the electrolyte.
[0058] In another exemplary embodiment, the content of the fluorine-based additive may be 2 parts by weight or less, preferably 1.8 parts by weight or less, more preferably 1.5 parts by weight or less, and may be 0.5 parts by weight or more or 1 part by weight or more, based on 100 parts by weight of the electrolyte.
[0059] When the fluorine-containing additive is included in the electrolyte, it serves to form a "film derived from F" on the silicon-based negative electrode. Therefore, as described above, even when the content of the fluorine-containing carbonate compound is the above parts by weight, the problem of gas generation can be solved.
[0060] In an exemplary embodiment of the present application, a lithium secondary battery is provided in which the fluorine-based additive is LiCF3COO or LiDFP.
[0061] LiDFP may refer to lithium difluorophosphate.
[0062] As described above, the fluorine-containing additive is reduced and decomposed, thereby forming a stable inorganic film component (LiF, Li2O, etc.) on the silicon-based negative electrode. In addition, by introducing the fluorine-containing additive, even if a limited amount (about 10%) of FEC (fluoroethylene carbonate) is used as a solvent for the electrolyte, a F-rich film that is beneficial to the silicon-based negative electrode is formed, thereby obtaining favorable room temperature performance characteristics.
[0063] The use of excess FEC as a solvent for the electrolyte (FEC 15% or more) is beneficial to room temperature performance, but is not feasible at high temperatures due to gas generation. Therefore, even when the use of FEC is limited, such as about 10%, a F-rich film can be formed by applying a Li salt-type additive together, and a film that is beneficial to the silicon-based negative electrode is formed instead of FEC, so that room temperature performance can be maintained.
[0064] In an exemplary embodiment of the present application, the electrolyte may include vinylene carbonate. In this case, the content of vinylene carbonate may be 0.3 parts by weight or less based on 100 parts by weight of the electrolyte.
[0065] In another exemplary embodiment, the content of vinylene carbonate may be 0.3 parts by weight or less, preferably 0.2 parts by weight or less, and may be 0 parts by weight or more or 0.1 parts by weight or more, based on 100 parts by weight of the electrolyte.
[0066] In the case of vinylene carbonate, when applied to a carbon-based negative electrode, the film-forming effect on the negative electrode is excellent, and as a result, no unreacted vinylene carbonate is left in the electrolyte and does not cause gas generation problems. However, in the case of a silicon-based negative electrode, the film-forming effect of vinylene carbonate on the negative electrode is not significant, and unreacted vinylene carbonate is oxidized at the positive electrode during charging, resulting in a rapid increase in gas generation.
[0067] Therefore, the electrolyte of the lithium secondary battery containing the silicon-based negative electrode according to the present application with the capacity characteristics maximized contains the vinylene carbonate in the above-mentioned content. When the content of vinylene carbonate is the above-mentioned parts by weight, vinylene carbonate together with the fluorine-containing additive enables to form a suitable film on the surface of the negative electrode, thereby reducing the amount of gas generated, and unreacted vinylene carbonate (VC) does not remain in the battery.
[0068] In the present application, the following lithium secondary battery is provided, in which the viscosity of the electrolyte at 25°C is 1.1 g / cm 3 The above, ion conductivity is 5.5 mS / cm or more.
[0069] In the present application, the viscosity of the electrolyte at 25°C may be 1.1 g / cm 3 The viscosity is preferably 1.11 g / cm2 at 25°C. 3 Above or the viscosity is 1.12 g / cm at 25°C 3 Above, and the viscosity at 25°C can be 2.0 g / cm 3 The viscosity is preferably 1.3 g / cm2 at 25°C.3 The viscosity is preferably 1.25 g / cm2 at 25°C. 3 the following.
[0070] In the present application, the electrolyte may have an ionic conductivity of 5.5 mS / cm or more, preferably 5.6 mS / cm or more, more preferably 5.7 mS / cm or more, and may be 6.5 mS / cm or less, specifically 6.3 mS / cm or less, more specifically 6.0 mS / cm or less at 25°C.
[0071] In the case of the electrolyte according to the present application, the ion conductivity within the above range can be ensured by containing the fluorine-containing carbonate compound as a solvent in the above-mentioned amount of parts by weight, and at the same time, the corresponding gas generation problem is solved by adjusting the content of vinylene carbonate and containing a specific content of the fluorine-containing additive, so that an electrolyte with suitable viscosity and ion conductivity can be obtained. For example, from the perspective of optimizing the lithium ion migration speed of high Ni NCM and silicon-based negative electrodes, the physical properties that the electrolyte of the present invention should have ensure the above viscosity and ion conductivity.
[0072] In an exemplary embodiment of the present application, the lithium salt is a material that is easily soluble in a non-aqueous electrolyte, and the lithium salt comprises a material selected from (CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - A group consisting of two or more anions.
[0073] In an exemplary embodiment of the present application, the lithium salt may include LiPF6 and LiFSI.
[0074] For the purposes of improving the life characteristics of the battery, suppressing the decline in battery capacity, and improving the discharge capacity of the battery, in addition to the above electrolyte components, the electrolyte may further contain one or more additives. For example, a halogenated alkylene carbonate compound such as difluoroethyl carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazoline, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride.
[0075] According to the present application, the silicon-based negative electrode may include a negative electrode current collector layer and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer.
[0076] The thickness of the negative electrode current collector layer is generally 1 μm to 100 μm. There is no particular limitation on such a negative electrode current collector as long as it has high electrical conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum cadmium alloy, etc. may be used. In addition, the negative electrode current collector layer may have micro-concavities and protrusions formed on the surface to enhance the bonding force with the negative electrode active material, and may be used in various different forms, such as a film, sheet, foil, net, porous body, foam body, or non-woven fabric body.
[0077] However, the thickness can be variously modified according to the type and use of the negative electrode used, and is not limited thereto.
[0078] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include a silicon-based active material.
[0079] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include one or more selected from the group consisting of a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.
[0080] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.
[0081] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloy.
[0082] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), and metal impurities, and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more.
[0083] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0084] In an exemplary embodiment of the present application, for the silicon-based active material, pure silicon (Si) may be particularly used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, as described above, based on a total of 100 parts by weight of the silicon-based active material, it contains pure Si particles (SiOx (x = 0)) that are not combined with other particles or elements within the above range.
[0085] Note that the average particle size (D50) of the silicon-based active material of the present invention may be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. If the average particle size is less than 5 μm, the specific surface area of the particles increases excessively, resulting in an excessive increase in the viscosity of the negative electrode slurry. Therefore, the particles constituting the negative electrode slurry cannot be smoothly dispersed. In addition, if the size of the silicon-based active material is too small, the contact area between the silicon particles and the conductive material in the negative electrode slurry composed of the conductive material and the binder decreases, increasing the possibility of disconnection of the conductive network, thereby reducing the capacity retention rate. On the other hand, if the average particle size is greater than 10 μm, there are excessively large silicon particles, making the surface of the negative electrode uneven, resulting in uneven current density during charge and discharge. In addition, if the silicon particles are too large, the phase stability of the negative electrode slurry becomes unstable, deteriorating the processability. As a result, the capacity retention rate of the battery decreases.
[0086] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.01 m 2 / g to 150.0 m 2 / g, more preferably 0.1 m 2 / g to 100.0 m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, most preferably 0.2 m2 / g to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).
[0087] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a silicon-containing film or coating.
[0088] In an exemplary embodiment of the present application, the content of the silicon-based active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.
[0089] In another exemplary embodiment, based on 100 parts by weight of the negative electrode active material layer composition, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less.
[0090] The negative electrode active material layer composition according to the present application uses a specific negative electrode conductive material and a negative electrode binder that can control the volume expansion rate during charge and discharge even when a significantly high capacity silicon-based active material is used within the above range. Therefore, even when the silicon-based active material is within the above range, the negative electrode active material layer composition does not deteriorate the performance of the negative electrode and has excellent output characteristics during charge and discharge.
[0091] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical shape, and the sphericity (roundness) thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0092] In the present application, sphericity is determined by the following Formula 1, where A is the area and P is the boundary line.
[0093] [Formula 1]
[0094] 4πA / P 2
[0095] In the related art, only graphite compounds are usually used as negative electrode active materials. However, in recent years, due to the increasing demand for high-capacity batteries, attempts to mix and use silicon-based compounds have increased in order to increase capacity. However, the silicon-based compounds are limited in that their volume expands rapidly during charge and discharge, resulting in damage to the conductive path formed in the negative electrode active material layer, thereby deteriorating the performance of the battery.
[0096] Therefore, in an exemplary embodiment of the present application, the negative electrode active material layer composition may include a negative electrode conductive material and a negative electrode binder. That is, the negative electrode conductive material plays a role in ensuring a conductive path, and the binder plays a role in retaining the negative electrode conductive material during charge and discharge.
[0097] In an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a surface-shaped conductive material, and a line-shaped conductive material.
[0098] In an exemplary embodiment of the present application, the dot-shaped conductive material refers to a conductive material that can be used to improve the conductivity of the negative electrode, which forms conductivity without causing chemical changes and has a round or dot shape. Specifically, the dot-shaped conductive material can be one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, preferably including carbon black in terms of high conductivity and excellent dispersibility.
[0099] In an exemplary embodiment of the present application, the BET specific surface area of the dot-shaped conductive material may be 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g or more and 60 m 2 / g or less.
[0100] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 40 nm to 60 nm.
[0101] In an exemplary embodiment of the present application, the conductive material may include a planar conductive material.
[0102] The planar conductive material refers to a conductive material that improves conductivity by increasing surface contact between silicon particles in the negative electrode and is used to suppress disconnection of conductive paths due to volume expansion. The planar conductive material may be a plate-shaped conductive material or a bulk-type conductive material.
[0103] In an exemplary embodiment of the present application, the planar conductive material may include one or more selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.
[0104] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. When the above range is met, sufficient particle size does not cause excessive increase in viscosity of the negative electrode slurry, resulting in easy dispersion. Therefore, when the same equipment and time are used for dispersion, the dispersion effect is excellent.
[0105] In an exemplary embodiment of the present application, a negative electrode composition is provided, in which the planar conductive material has a D10 of 0.5 μm to 1.5 μm, a D50 of 4.0 μm to 5.0 μm, and a D90 of 7.0 μm to 15.0 μm.
[0106] In an exemplary embodiment of the present application, as the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area or a low specific surface area planar conductive material may be used.
[0107] In an exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without limitation. However, in particular, the planar conductive material according to the present application may be affected by dispersion to a certain extent in terms of electrode performance, so it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause problems in dispersion.
[0108] In an exemplary embodiment of the present application, the BET specific surface area of the planar conductive material may be 1 m 2 / g or above.
[0109] In another exemplary embodiment, the BET specific surface area of the planar conductive material may be 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m 2 / g or less.
[0110] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 250 m 2 / g or less.
[0111] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g and above 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.
[0112] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may contain a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" herein refers to a secondary shape in which a plurality of carbon nanotube units are arranged side by side or are wound in a bundle or rope-like manner so that the longitudinal axis orientations of the carbon nanotube units are substantially the same. The carbon nanotube unit has a cylindrical graphite sheet with a nanometer-sized diameter and has an sp2 bonding structure. In this case, depending on the curling angle and structure of the graphite sheet, the characteristics of a conductor or a semiconductor may be exhibited. Compared with the wound carbon nanotubes, the bundle-type carbon nanotubes can be more evenly dispersed during the manufacture of the negative electrode, and can more smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.
[0113] In an exemplary embodiment of the present application, the negative electrode conductive material may include a linear conductive material, and the linear conductive material may be a carbon nanotube.
[0114] In an exemplary embodiment of the present application, the carbon nanotube may be SWCNT or / and MWCNT. When the linear conductive material is SWCNT, the length of the SWCNT may be 0.5 μm to 100 μm, preferably 1 μm to 80 μm.
[0115] In an exemplary embodiment of the present application, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0116] In another exemplary embodiment, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less, preferably 5 parts by weight or more and 30 parts by weight or less, and more preferably 5 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.
[0117] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material and a linear conductive material, and a ratio of the planar conductive material to the linear conductive material may satisfy 1:0.001 to 1:0.3.
[0118] In an exemplary embodiment of the present application, since the negative electrode conductive material comprises the planar conductive material and the linear conductive material and respectively satisfies the above-mentioned composition and ratio, the life characteristics of the existing lithium secondary battery are not significantly affected, and the number of sites at which the battery can be charged and discharged is increased, so that the output characteristics are excellent at a high C rate.
[0119] The composition of the negative electrode conductive material according to the present application is completely different from that of the conductive material used for the positive electrode. That is, the negative electrode conductive material according to the present application is used to maintain contact between the silicon-based active materials whose electrode volume expands greatly due to charge and discharge, while the positive electrode conductive material is used to provide a certain conductivity while playing a buffering role during rolling, and is completely different from the negative electrode conductive material of the present invention in terms of composition and function.
[0120] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material, and its composition is completely different from that of the conductive material applied to the graphite-based active material. That is, since the conductive material used for the electrode with the graphite-based active material has only smaller particles than the active material, the conductive material has the characteristics of improving the output characteristics and imparting a certain conductivity, and is completely different from the negative electrode conductive material applied together with the silicon-based active material in the present invention in terms of composition and function.
[0121] In an exemplary embodiment of the present application, the structure and function of the plate-shaped conductive material used as the above-mentioned negative electrode conductive material are different from the structure and function of the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material processed into a spherical or dot-like shape for use to promote the storage and release of lithium ions.
[0122] On the other hand, the plate-like conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the plate-like conductive material is a material contained in order to maintain a conductive path in the negative electrode active material layer, and refers to a material for securing a conductive path in a planar shape within the negative electrode active material layer, rather than a material for storing and releasing lithium.
[0123] That is, in the present application, using plate-like graphite as a conductive material means that graphite is processed into a planar or plate-like shape and used as a material that ensures a conductive path rather than a material that functions to store or release lithium. In this case, the negative electrode active material contained together has high capacity characteristics in terms of storing and releasing lithium, and is used to store and release all lithium ions transferred from the positive electrode.
[0124] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.
[0125] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.
[0126] The negative electrode binder according to an exemplary embodiment of the present application is used to retain the silicon-based active material and the negative electrode conductive material to prevent distortion and structural deformation of the negative electrode structure when the volume of the silicon-based active material expands and relaxes. As long as such a role is met, all conventional negative electrode binders can be applied. Specifically, an aqueous binder can be used, and more specifically, a PAM-based binder can be used.
[0127] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may be 5 parts by weight or more, 8 parts by weight or more, based on 100 parts by weight of the negative electrode active material layer composition.
[0128] Compared with the existing carbon-based negative electrode, when using a Si-based negative electrode, the aqueous binder is applied in the above-mentioned weight parts, so that a dot-shaped conductive material with a low functional group content can be used. In addition, the above-mentioned characteristics make the dot-shaped conductive material hydrophobic and make the bonding strength between the conductive material / binder excellent.
[0129] In an exemplary embodiment of the present application, the silicon-based negative electrode may be formed by coating a negative electrode slurry including the negative electrode active material layer composition on one surface or both surfaces of the negative electrode current collector layer.
[0130] In an exemplary embodiment of the present application, the negative electrode slurry may include a negative electrode active material layer composition and a slurry solvent.
[0131] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy a range of 5% or more and 40% or less.
[0132] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.
[0133] The solid content of the negative electrode slurry may mean the content of the negative electrode composition contained in the negative electrode slurry, and may mean the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0134] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, so that the aggregation of particles of the negative electrode composition is minimized, thereby effectively forming the negative electrode active material layer.
[0135] In an exemplary embodiment of the present application, the slurry solvent may be used without limitation as long as it can disperse the negative electrode composition, and specifically, water or NMP may be used.
[0136] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.
[0137] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0138] The porosity varies depending on the composition and content of the silicon-based active material, conductive material and binder contained in the negative electrode active material layer. In particular, when the silicon-based active material and conductive material according to the present application are contained in a specific composition and content, they satisfy the above ranges so that the conductivity and resistance of the electrode are within an appropriate range.
[0139] In an exemplary embodiment of the present application, the positive electrode includes a positive electrode collector layer and a positive electrode active material layer provided on one surface or both surfaces of the positive electrode collector layer.
[0140] In an exemplary embodiment of the present application, the positive electrode active material layer may include a positive electrode active material layer composition, and the positive electrode active material layer composition may include one or more selected from the group consisting of a positive electrode active material, a positive electrode conductive material, and a positive electrode binder.
[0141] In the positive electrode, there is no particular restriction on the positive electrode collector layer, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., etc. can be used. In addition, the thickness of the positive electrode collector layer can generally be 1 to 500 μm, and the surface of the positive electrode collector layer can be formed with microscopic concave-convex to enhance the adhesion with the positive electrode active material. For example, the positive electrode collector layer can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0142] In an exemplary embodiment of the present application, a lithium secondary battery is provided in which the thickness of the positive electrode collector layer and the negative electrode collector layer is 1 μm or more and 100 μm or less, and the thickness of the positive electrode active material layer and the negative electrode active material layer is 20 μm or more and 500 μm or less.
[0143] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include a material selected from the group consisting of LiNi x Co y Mn z O2 (x+y+z=1), LiNi a Co b Mn c Al d O2(a+b+c+d=1)、LiMn2O4、LiNi 0.5 Mn 1.5 O2 and LiM x Fe yOne or more of the group consisting of PO4 (M: transition metal, x+y=1). In this case, the positive electrode active material is not limited thereto.
[0144] Specifically, as the positive electrode active material, commonly used NCM or NCMA may be used.
[0145] Typically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound substituted by one or more transition metals; lithium iron oxide such as LiFe3O4; lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5 and Cu2V2O7; 1-c2 M c2 Ni-site lithium nickel oxide represented by the chemical formula LiMn 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.6) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4 in which part of Li in the chemical formula is replaced by alkaline earth metal ions, etc., but is not limited thereto. The positive electrode may be Li metal.
[0146] In an exemplary embodiment of the present application, the positive electrode active material includes a lithium composite transition metal compound containing nickel (Ni), cobalt (Co) and manganese (Mn), and the lithium composite transition metal compound includes single particles or secondary particles, and the average particle size (D50) of the single particles can be greater than 1 μm.
[0147] For example, the average particle size (D50) of the single particles may be 1 μm to 12 μm, 1 μm to 8 μm, 1 μm to 6 μm, greater than 1 μm to 12 μm, greater than 1 μm to 8 μm, or greater than 1 μm to 6 μm.
[0148] Even when single particles are formed with a small average particle size (D50) of 1 μm or more and 12 μm or less, particle strength can be excellent. 2When the roller is rolled with a force of 650 kgf / cm, the particle strength of the single particle can be 100 to 300 MPa. 2 When the single particle is rolled with a strong force, the phenomenon of increase of fine particles in the electrode due to particle breakage is also alleviated, which improves the life characteristics of the battery.
[0149] The single particle may be produced by mixing a transition metal precursor and a lithium source material and firing. The secondary particle may be produced by a different method from the single particle, and its composition may be the same as or different from that of the single particle.
[0150] The method of forming the single particles is not particularly limited, but may generally be formed by overfiring at an elevated firing temperature, or may be produced by using an additive that assists overfiring such as a grain growth promoter, or by changing a starting material.
[0151] For example, the firing is carried out at a temperature at which a single particle can be formed. For this reason, the firing should be carried out at a temperature higher than the temperature during the manufacture of the secondary particles. For example, when the composition of the precursor is the same, the firing should be carried out at a temperature about 30°C to 100°C higher than the temperature during the manufacture of the secondary particles. The firing temperature for forming the single particle can vary according to the metal composition in the precursor. For example, when a single particle is formed with a high NiNCM lithium composite transition metal oxide having a nickel (Ni) content of 80 mol % or more, the firing temperature can be about 700°C to 1000°C, preferably about 800°C to 950°C. When the firing temperature satisfies the above range, a positive electrode active material containing a single particle with excellent electrochemical performance can be manufactured. If the firing temperature is lower than 790°C, a positive electrode active material containing a lithium composite transition metal compound in the form of a secondary particle can be manufactured. If the firing temperature exceeds 950°C, over-firing occurs, and a layered crystal structure is not properly formed, so that the electrochemical characteristics may deteriorate.
[0152] In this specification, the single particle is a term used to distinguish from typical secondary particles produced by aggregation of tens to hundreds of primary particles, and is a concept including single particles composed of one primary particle and quasi-single particle forms that are aggregates of 30 or less primary particles.
[0153] Specifically, in the present invention, the single particle may be a single particle consisting of one primary particle, or a quasi-single particle form that is an agglomerate of 30 or less primary particles, and the secondary particle may be an agglomerate of hundreds of primary particles.
[0154] In an exemplary embodiment of the present application, the lithium composite transition metal compound as the positive electrode active material further includes secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.
[0155] In the present invention, the single particle may be a single particle consisting of one primary particle, or a quasi-single particle that is an agglomerate of 30 or less primary particles, and the secondary particle may be an agglomerate of hundreds of primary particles.
[0156] The lithium composite transition metal compound may further include secondary particles. The secondary particles are formed by agglomeration of primary particles, and can be distinguished from the concept of single particles including one primary particle, one single particle, and a quasi-single particle that is an agglomerate of 30 or less primary particles.
[0157] The particle size (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles may be 0.05 m 2 / g to 10 m 2 / g, preferably 0.1 m 2 / g to 1 m 2 / g, more preferably 0.3 m 2 / g to 0.8 m 2 / g.
[0158] In another exemplary embodiment of the present application, the secondary particles are agglomerates of primary particles, and the average particle size (D50) of the primary particles is 0.5 μm to 3 μm. Specifically, the secondary particles may be agglomerated forms of hundreds of primary particles, and the average particle size (D50) of the primary particles may be 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.
[0159] When the average particle size (D50) of the primary particles satisfies the above range, a single-particle positive electrode active material with excellent electrochemical properties can be formed. If the average particle size (D50) of the primary particles is too small, the number of agglomerates of the primary particles forming the lithium nickel oxide particles increases, thereby reducing the effect of suppressing particle breakage during rolling. If the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles may be extended, thereby increasing resistance and deteriorating output characteristics.
[0160] According to another exemplary embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles. As a result, even if the formed single particles have a small particle size, they can have excellent particle strength, and therefore, the phenomenon of increasing particles in the electrode due to particle rupture is alleviated, which can improve the life characteristics of the battery.
[0161] In an exemplary embodiment of the present application, an average particle diameter (D50) of the single particles is 1 μm to 18 μm smaller than an average particle diameter (D50) of the secondary particles.
[0162] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm, 1.5 μm to 15 μm, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.
[0163] When the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, for example, when the above-mentioned range is met, even if the formed single particles have a small particle size, they can have excellent particle strength. As a result, the phenomenon of increased microparticles in the electrode due to particle breakage is alleviated, which improves the life characteristics and energy density of the battery.
[0164] According to another exemplary embodiment of the present application, based on 100 parts by weight of the positive electrode active material, the content of the single particle is 15 parts by weight to 100 parts by weight. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 20 parts by weight to 100 parts by weight, or 30 parts by weight to 100 parts by weight.
[0165] For example, based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 100 parts by weight or less.
[0166] When the single particles are included within the above range, excellent battery characteristics can be exhibited when combined with the above negative electrode material. In particular, when the content of the single particles is 15 parts by weight or more, the phenomenon of increasing fine particles in the electrode due to particle rupture in the rolling process after manufacturing the electrode can be alleviated, which can improve the life characteristics of the battery.
[0167] In an exemplary embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the content of the secondary particles may be 85 parts by weight or less based on 100 parts by weight of the positive electrode active material. Based on 100 parts by weight of the positive electrode active material, the content of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less. Based on 100 parts by weight of the positive electrode active material, the content of the secondary particles may be 0 parts by weight or more.
[0168] When the above range is met, the above effect due to the presence of the single particle in the positive electrode active material can be maximized. In the case of a positive electrode active material containing the secondary particles, its composition may be the same as or different from the composition exemplified in the above single particle positive electrode active material, and may refer to an agglomerated form of a single particle.
[0169] In an exemplary embodiment of the present application, the content of the positive electrode active material in 100 parts by weight of the positive electrode active material layer may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and most preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0170] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.
[0171] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constituted. Specific examples may include graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and the like, and any one of them or a mixture of two or more thereof may be used.
[0172] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one of them or a mixture of two or more thereof may be used.
[0173] The diaphragm is used to separate the negative electrode from the positive electrode and provide a migration path for lithium ions, wherein any diaphragm can be used as the diaphragm without particular limitation, as long as it is commonly used in secondary batteries, in particular, it is preferred to use a diaphragm with high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, a common porous non-woven fabric can be used, such as a non-woven fabric formed of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm with a single-layer or multilayer structure can be selectively used.
[0174] Invention Mode
[0175] Hereinafter, preferred embodiments will be provided in order to better understand the present invention. It will be apparent to those skilled in the art that the embodiments are provided only to illustrate the present invention, and various modifications and changes may be made within the scope and technical spirit of the present invention. Such modifications and changes naturally fall within the scope of the claims contained herein.
[0176] <Production Example>
[0177] (1) Manufacturing of positive electrode
[0178] Using Li(Ni a Co b Mn c )O2 is used as the positive electrode active material.
[0179] In this case, the NCM of the positive electrode active material other than lithium (Li) and oxygen (O2) has a ratio of Ni:Co:Mn = 93:5:2, thereby satisfying a ratio of a:b:c = 93:5:2 (a:b:c = 0.93:0.05:0.02). In addition, D50 is 3.8 μm, Dmin and Dmax are 1.2 μm and 13 μm, and the BET specific surface area is 0.64 m 2 , true density is 4.78 to 4.80 g / cm 3 .
[0180] The positive electrode active material, the positive electrode conductive material (LB. CNT) and the binder (PVdF, KF9700) were added to a solvent (N-methylpyrrolidone, NMP) at a weight ratio of 97.96:0.8:1.24 to prepare a positive electrode slurry. The positive electrode slurry was applied to an aluminum (Al) film having a thickness of 25 μm as a positive electrode current collector, dried, and then rolled to prepare a positive electrode.
[0181] (2) Manufacturing of negative electrode
[0182] A negative electrode active material layer composition was prepared using Si (average particle size (D50): 5 μm) as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder at a weight ratio of 80:9.6:0.4:10. A negative electrode slurry (solid concentration: 28 wt %) was prepared by adding the composition to distilled water as a solvent for forming a negative electrode slurry.
[0183] The first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is carbon nanotubes.
[0184] As a mixing method, the slurry was prepared by dispersing the first conductive material, the second conductive material, the binder, and water at 2500 rpm for 30 minutes using a homomixer, adding the active material thereto, and dispersing the resulting mixture at 2500 rpm for 30 minutes.
[0185] The negative electrode slurry was prepared at 3.00 mg / cm 2 A loading amount of 200 Å was coated on both surfaces of a copper current collector (thickness: 15 μm) serving as a negative electrode current collector, which was then roll-pressed and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 23 μm).
[0186] (3) Manufacturing of secondary batteries
[0187] The electrode assembly was manufactured by interposing a compression-resistant thin film separator (PE, 12 μm) having a 3 μm / 3 μm ceramic coating between the positive electrode and the negative electrode. After the electrode assembly was placed in a case, an electrolyte was injected into the case, thereby manufacturing a lithium secondary battery.
[0188] In this case, the electrolyte satisfies the composition and content shown in Table 1 below.
[0189]
[0190] Experimental Example 1: Lifespan Evaluation
[0191] For the lithium secondary battery containing the negative electrode manufactured in the embodiment and the comparative example, the life and capacity retention rate were evaluated using an electrochemical charge and discharge device. The secondary battery was subjected to an in-situ cycle test at 4.2-3.2 V and 1C / 1C, during which 1C / 1C charge and discharge (4.2-3.2 V) was performed every 50 cycles to measure the capacity retention rate, and the results are listed in Table 2.
[0192] Capacity retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the first cycle)} × 100
[0193] Experimental Example 2: Evaluation of resistance increase rate measurement value
[0194] In Experimental Example 1, during the test, after the battery was charged and discharged at 1C / 1C (4.2-3.2 V) every 50 cycles to measure the capacity retention rate, the battery was discharged at 2.5 C pulse at SOC 50 to measure the resistance, and then the resistance increase rate was compared and analyzed. The results are shown in Table 2 below.
[0195] Experimental Example 3: Volume change due to gas generation using bag test
[0196] For the lithium secondary batteries including the negative electrodes manufactured in the embodiments and comparative examples, after the pouch cells with a capacity of 1 Ah were fully charged to 4.2 V at 0.33 C, the cells were stored in an oven at 60° C. for 8 weeks. Thereafter, after fully discharging to 2.5 V, the gas generated in the pouch cells was extracted using the GC / MS method and the gas quantitative analysis was performed, and the results are listed in Table 2 below.
[0197]
[0198] In Examples 1 to 3 according to the present application, the content of vinylene carbonate is adjusted, and an additive that forms an effective film on the silicon-based negative electrode is included, thereby confirming that the problem that vinylene carbonate does not form an effective film on the silicon-based negative electrode and remains and a large amount of gas is generated due to the oxidation reaction at the positive electrode can be solved. Therefore, it can be confirmed that the lithium secondary battery according to the present application has the characteristics of reducing the amount of gas generated even during long-term storage at high temperatures to ensure performance and ensure ion conductivity.
[0199] In Comparative Example 1 in which the content of the carbonate compound containing a fluorine group was less than 10 parts by weight based on 100 parts by weight of the solvent, it was confirmed that no effective film was formed on the negative electrode, and thus the capacity retention rate decreased and the resistance increase rate increased.
[0200] Comparative Example 2 corresponds to the case where the fluorine-based additive according to the present application is not included. In this case, it can be confirmed that an excessive amount of FEC is included, so the gas generation amount increases rapidly at high temperatures, resulting in a large volume change rate and a decrease in life performance.
[0201] Comparative Example 3 corresponds to the case where the fluorine-containing additive according to the present application is included but the content of vinylene carbonate exceeds the range according to the present application. In the case of Comparative Example 3 using a silicon-based negative electrode, it can be confirmed that vinylene carbonate does not form an effective film on the negative electrode and remains, and a large amount of gas is generated due to the oxidation reaction at the positive electrode, thereby increasing the amount of gas generated compared to the examples, thereby reducing the capacity retention rate and increasing the resistance increase rate.
[0202] Comparative Examples 4 to 6 each correspond to a case where the fluorine-containing additive according to the present application is not included and the content of vinylene carbonate is adjusted. In this case, it can also be confirmed that due to the inclusion of FEC, the gas generation amount increases rapidly at high temperatures, resulting in a large volume change rate and a decrease in life performance.
Claims
1. A lithium secondary battery comprising: positive electrode; Silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and Electrolytes, The silicon-based negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer. wherein the negative electrode active material layer comprises a negative electrode active material layer composition, wherein the negative electrode active material layer composition contains a silicon-based active material, and the silicon-based active material contains one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloys, wherein the electrolyte comprises a solvent, a lithium salt, a fluorine-based additive and vinylene carbonate (VC), wherein the content of the vinylene carbonate is less than 0.3 parts by weight based on 100 parts by weight of the electrolyte, wherein the content of the carbonate compound containing a fluorine group is 10 parts by weight or more based on 100 parts by weight of the solvent, and The content of the fluorine-based additive is less than 2 parts by weight based on 100 parts by weight of the electrolyte. 2 . The lithium secondary battery according to claim 1 , wherein when the lithium secondary battery is stored at 60° C. for 8 weeks, a gas generation amount per unit capacity is 5 ml / Ah or less.
3. The lithium secondary battery according to claim 1, wherein the fluorine-based additive is LiCF3COO. 4 . The lithium secondary battery according to claim 1 , wherein the solvent is a mixed solvent containing two carbonate-based compounds.
5. The lithium secondary battery according to claim 1, wherein the lithium salt comprises a compound selected from (CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - A group consisting of two or more anions.
6. The lithium secondary battery according to claim 1, wherein the silicon-based active material contains one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), and metal impurities, and based on 100 parts by weight of the silicon-based active material, the content of SiO x (x = 0) is 70 parts by weight or more. 7 . The lithium secondary battery according to claim 1 , wherein the content of the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.
8. The lithium secondary battery according to claim 1, wherein the positive electrode comprises a positive electrode current collector layer and a positive electrode active material layer provided on one surface or both surfaces of the positive electrode current collector layer, wherein the positive electrode active material layer comprises a positive electrode active material layer composition, wherein the positive electrode active material layer composition comprises a positive electrode active material, and The positive electrode active material comprises a material selected from the group consisting of LiNi x Co y Mn z O2 (x+y+z=1), LiNi a Co b Mn c Al d O2(a+b+c+d=1)、LiMn2O4、LiNi 0.5 Mn 1.5 O2 and LiM x Fe y One or more of the group consisting of PO4 (M: transition metal, x+y=1).
9. The lithium secondary battery according to claim 8, wherein the thickness of the positive electrode current collector layer and the negative electrode current collector layer is each 1 μm or more and 100 μm or less, and The thickness of the positive electrode active material layer and the negative electrode active material layer is each 20 μm or more and 500 μm or less.
10. The lithium secondary battery according to claim 1, wherein the viscosity of the electrolyte at 25°C is 1.1 g / cm 3 The above, ion conductivity is 5.5 mS / cm or more.
Citation Information
Patent Citations
Anode for lithium ion battery
JP2009080971A